Impact of COVID-19 Induced Lockdown on Health and Education: A Survey Based Study - Singh, Alka; Singh, Vibha; Nayak, Sanatan (Innovative Journal of Medical and Health Sciences, 2020)
Background & Objectives: The COVID-19 pandemic has created significant effect on well-being, health, economic and social system of the country. However, dearth of studies has explored the effect of COVID-19 individual as well as social system. Therefore, the study aimed to assess the effect of COVID-19 on psychological and physical health of individual and educational system. Methods: An online questionnaire that assesses the individual perspective about effect of COVID-19 on health and educational system was framed and was filled by 400 participants. From this, 20 questionnaires were invalid or not completed. Therefore the data of 380 participants were presented using descriptive statistics. Results: Most respondents were male, 15 to 30 years of age, post graduated, single, and working in agriculture sector. Most of the respondents have monthly income of less than 20,000 and expenditure of 5000 and above. Participants have agreed with the statement that monthly income, education has affected and savings, addiction or smoking got decreased during lockdown. Food habits have been changed. Health problems, practicing vipasyana, level of stress, and internet surfing has increased during lockdown. People were spending their most of the time with family during lockdown. Daily wage workers were most affected group in this pandemic induced lockdown situation. Conclusion: COVID-19 has impacted education system. This lockdown situation has affected physical and psychological health, economic condition of individuals. These impacts should be considered in policy making related to these areas in this pandemic situation. Keywords: Covid-19, Lockdown; descriptive statistics, India, Education, Health, Psychological, Stress.